2018
DOI: 10.1016/j.neuron.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

RNP-Granule Assembly via Ataxin-2 Disordered Domains Is Required for Long-Term Memory and Neurodegeneration

Abstract: Human Ataxin-2 is implicated in the cause and progression of amyotrophic lateral sclerosis (ALS) and type 2 spinocerebellar ataxia (SCA-2). In Drosophila, a conserved atx2 gene is essential for animal survival as well as for normal RNP-granule assembly, translational control, and long-term habituation. Like its human homolog, Drosophila Ataxin-2 (Atx2) contains polyQ repeats and additional intrinsically disordered regions (IDRs). We demonstrate that Atx2 IDRs, which are capable of mediating liquid-liquid phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 97 publications
12
125
0
Order By: Relevance
“…Previous studies suggested that the IDLs of adjacent SSB molecules can interact with each other to enhance the cooperativity of ssDNA binding, while the IDL was also proposed to interact with the OB fold Kozlov et al, 2015Kozlov et al, , 2017. Moreover, the central role played by similar low-sequence-complexity, Gln/Gly/Pro-rich IDRs in previously investigated LLPS systems (Bakthavachalu et al, 2018;Mannen et al, 2016;Milovanovic et al, 2018;Sabari et al, 2018) as well as the predicted LLPS propensities suggest a role for the IDL in SSB LLPS ( Fig. 1B-D).…”
Section: Multivalent Interactions Between Ssb Idl Regions Are Requirementioning
confidence: 57%
“…Previous studies suggested that the IDLs of adjacent SSB molecules can interact with each other to enhance the cooperativity of ssDNA binding, while the IDL was also proposed to interact with the OB fold Kozlov et al, 2015Kozlov et al, , 2017. Moreover, the central role played by similar low-sequence-complexity, Gln/Gly/Pro-rich IDRs in previously investigated LLPS systems (Bakthavachalu et al, 2018;Mannen et al, 2016;Milovanovic et al, 2018;Sabari et al, 2018) as well as the predicted LLPS propensities suggest a role for the IDL in SSB LLPS ( Fig. 1B-D).…”
Section: Multivalent Interactions Between Ssb Idl Regions Are Requirementioning
confidence: 57%
“…Evidence has been accumulating that RNP granules are incubators for the formation of pathogenic protein aggregates associated with neurodegenerative disease. It has been proposed that localization of proteins such as TDP-43, FUS and C9OFR72-encoded dipeptide repeat GR50 in high concentration in stress granules likely in a gel form, promotes their conversion into pathogenic amyloid-like aggregates [78][79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…This was accomplished with the aid of ATXN2, an RNP-protein that is required for RNP-granule formation. Three ALS associated proteins, TDP-43, FUS and C9OFR72-encoded dipeptide repeat GR50, have been shown to co-localize with ATXN2 RNP granules [42,78] in yeast, human or Drosophila S2 cells. Also, either reducing the level of ATXN2 or deleting one of its intrinsically disordered regions both reduced RNP-granule formation and reduced neurodegeneration caused by TDP-43, C9ORF72 dipeptide or FUS [78,[83][84][85].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulatory regions can also promote LLPS by mediating intermolecular interactions (with proteins, RNA, or DNA). For example, in the memory‐associated ataxin‐2 homolog (Atx2) that accumulates in SGs on arsenite stress, the C‐terminal IDR is the PDR, while the RNA‐binding middle IDR is dispensable for LLPS . Cellular expression of GFP‐Atx2 deletion constructs, however, showed that both IDRs are essential for normal SG formation and long‐term habituation .…”
Section: Regulation By Elements Within the Phase‐separating Proteinmentioning
confidence: 99%